Faktor-Faktor yang mempengaruhi Petani dalam Penggunaan Benih Berlabel Bahasa Asing (BBBA) - Bekti Wahyu Utami; Suminah Suminah (Caraka Tani: Journal of Sustainable Agriculture, 2005)
To increase product need the existence of preeminent seed, because seed represent one of the crop conducting medium having role which very determine in the effort increase product and quality of crop conducting result. Seed claimed to be gilt edged where usage of seed with quality for supported by technological medium going forward other will be able to yield maximal productive crop. The farmers often loss their energy and also time in usage of seed which its unfavorable quality.The aimed of this research is to know how accurate factors such as wide of farm, education, seed price, and manure to influence farmer using BBBA (seed in foreign language’s label) at Sukoharjo District. Framework idea in this research is at taking an action, to buy and also use something, farmer will influence by immeasurable of factor, internal and external factor. Internal factor is direct related factor in accurate matter, and external factor related to BBBA consumer. In this research which the included in internal factor is BBBA it self price and usage of manure, while external factor of wide of farm mastered by farmers cultivated melon, formal education and of them.Sample area was selected by purposive pursuant to usage of farm many by farmer for the conducting of melon. Sample taken by counted 60 person who is taken at random. Data analysis is doubled linear regression.Result of regresi analysis mention that at confidence level 95% passing Test F obtained that accurate variable-variable by together mount usage of BBBA, where R2 value equal to 0,601 meaning that variation of usage BBBA influenced by free variable in model equal to 60,1%. And through Test T variable having an effect on wide of farm, Manure anad education with biggest influence sequence is usage of manure, later than education and wide of farm. While BBBA itself price in the reality do not influence farmer in using the BBBA product.